Risk Management for 4-H Youth Development Work: Pre-event Planning Guide and Matrix - Dale Pracht; Paula M. Davis; Stefanie Prevatt; Janet Psikogios; Marilyn Norman; Kate Fogarty; Jean Hink (EDIS)
This is the first publication in the Risk Management for 4-H Youth Development Work series. This series is intended to prepare UF/IFAS Extension county faculty, staff, volunteers, and youth for the important task of providing best practices in risk management strategies. This 5-page fact sheet discusses the matrix, levels of risk, probability that something will go wrong, modifications to the event or activity, and post-event assessment. Written by Dale Pracht, Paula Davis, Stefanie Prevatt, Janet Psikogios, Marilyn Norman, Kate Fogarty, and Jean Hink, and published by the UF/IFAS 4-H Youth Development Department, revised March 2018. http://edis.ifas.ufl.edu/4h299